Pengembangan Modul Biologi Dasar berbasis keterampilan proses sains - Nurhayati B.; Abdul Hadis; Faisal Faisal (Seminar Nasional LP2M UNM, 2019)
It can not be denied that the facts in the society indicate that the graduate who have undergraduate status, most of them still have the status of ready-to-train workers, not ready to work, until produce unemployment whose number has reached 944,666 people. Even the alumnus of vocational schools and specialties are more ready to use in the society. This phenomenon occurs because the learning system in universities, is still dominant using lecture methods rather than process skills, consequently students generally cognitive level is at the level of knowledge and understanding, weak in terms of application, analysis, synthesis, and evaluation with divergent thinking. To overcome this phenomenon, the application of process skills for all courses in universities, especially in Basic Biology course for Biology Department students is very urgent done in an integrated, comprehensive, and sustainable. Therefore, it is necessary to develop science-based learning tools on the Basic Biology course as a learning medium that can provide ease of learning for students, which in turn can improve the quality of process and learning outcomes in the classroom, in the laboratory, and in other learning areas.